Konseling Individu dengan Teknik Cognitive Restructuring dalam Mengatasi Depresi pada Remaja Korban Broken Home - Cindy Julita Sari; Zhila Jannati (Journal of Society Counseling, 2025)
This study is entitled "The application of individual counseling with cognitive restructuring techniques in overcoming depression in adolescent victims of broken homes (case study on client T on Talang Ratu Road, Palembang). Depression in adolescent victims of broken homes is one of the problems that needs to be handled seriously. This study aims to test the effectiveness of the application of individual counseling with Cognitive Restructuring techniques in overcoming depression in adolescent victims of broken homes. This case study was conducted on client T, who is eighteen years old and a victim of a broken home on Talang Ratu Road, Palembang, Ganges of Peace, Palembang. This study uses a descriptive qualitative method, namely, data collected in the form of words, pictures, not numbers. The subjects in this study were eighteen-year-old adolescents who were adolescents on Talang Ratu Road, Palembang, Ganges of Peace one, Palembang. The data collection techniques used were observation, interviews, and documentation. While the data analysis techniques used were data reduction, data presentation, and verification. The results of the study showed that before individual counseling activities with the Cognitive Restructuring technique were carried out, adolescents always locked themselves away and did not socialize, which caused symptoms of depression, due to the divorce of their parents, which could make adolescents lose direction in their previous lives. However, after individual counseling activities with the cognitive restructuring technique were carried out for four meetings, it could reduce symptoms of depression in client "T". The client showed positive changes in thought patterns, feelings, and behavior after undergoing counseling. This study proves that individual counseling with the Cognitive Restructuring technique can be an alternative in overcoming depression in adolescent victims of broken homes.